ANALYSIS OF THE EFFECT OF INITIAL WATER TEMPERATURE ON CLOVE OIL DISTILLATION TIME - AZMAIN N. HATUWE; ALEXANDER A.PATTY; NOCE N. TETELEPTA; SEMUEL M. TARIBUKA (CV KULTURA DIGITAL MEDIA, 2022)
The oil contained in clove leaves can be taken through the distillation process. The distillation process is carried out to separate the clove oil from the water contained in the leaves. The kettle operated is 2.5 meters high and 2 meters in diameter. The inner side of the kettle is divided into 2 rooms, at the bottom with a height of 1 meter filled with water and at the top with a height of 1.5 meters filled with clove leaves. The loading capacity of clove leaves is 1 ton and the water required is 2.5 m3. With the length of time the clove oil refining process lasts for 8 hours. Without changing the equipment specifications, efforts can be made to shorten the production time, by increasing the enhancer temperature above 26 oC. Data sourced from the distillation equipment specifications are needed to analyze the amount of energy required during the distillation process, as well as the determination of the distillation time. The analysis was carried out with 3 stages of variation of the initial water enhancer temperature of 26 oC, 50 oC and 75 oC. The temperature of the replacement water entered into the kettle is 26 oC, resulting in a distillation time of clove oil for 8 hours. When the replacement water temperature was increased by 50 oC, the distillation time was 7.89 hours. The more the enhancing water temperature is increased by 75 oC, the distillation time decreases to 7.786 hours. Thus, the distillation process time of clove oil can be shortened by increasing the initial temperature degree of the replacement water.